Constructions of time and history in the pre-Columbian Andes (Boulder)
xiv, 288 sayfa
Keywords: “Constructions of Time and History in the Pre-Columbian Andes explores archaeological approaches to temporalities, social memory, and constructions of history in the pre-Columbian Andes. The authors examine a range of Indigenous temporal experiences and ideologies, including astronomical, cyclical, generational, eschatological, and mythical time. This nuanced, interdisciplinary volume challenges outmoded anthropological theories while building on an emic perspective to gain greater understanding of pre-Columbian Andean cultures. Contributors to the volume rethink the dichotomy of past and present by understanding history as indigenous Andeans perceived it--recognizing the past as a palpable and living presence. We live in history, not apart from it. Within this framework time can be understood as a current rather than as distinct points, moments, periods, or horizons. The Andes offer a rich context by which to evaluate recent philosophical explorations of space and time. Using the varied materializations and ritual emplacements of time in a diverse sampling of landscapes, Constructions of Time and History in the Pre-Columbian Andes serves as a critique of archaeology's continued and exclusive dependence on linear chronologies that obscure historically specific temporal practices and beliefs.” --